Slametan and Social Piety among Indonesian Sap Tappers: Ritual, Labor Solidarity, and Javanese Ethics - Wahyu Triani; Titis Srimuda Pitana; Prasetyo Adi Wisnu Wibowo (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
In Javanese society, slametan has long functioned not only as a religious ritual but also as a cultural mechanism for maintaining social harmony, solidarity, and collective identity. This study analyzes the meaning and function of slametan as a form of social piety within the Galih Warangka Jati Association. Using a descriptive qualitative approach, the research gathered data through in-depth interviews and observations. The analysis was conducted using the perspectives of social piety and Javanese ethics to examine the interrelationship between religion and culture in the lives of penderes ‘sap tappers’. The results show that the penderes ‘sap tappers’ perform various types of slametan, including 1 Sura, takiran, wetonan, telasan, mulud, life-cycle rituals (birth and death), and celebrations (hajatan). The diversity of these rituals indicates that slametan accompanies various important personal and communal phases of life. Furthermore, the tradition reflects social piety through solidarity and togetherness. These values align with Javanese ethics, which emphasize the principles of harmony ‘guyub rukun’ and respect ‘hormat’ to maintain social balance. This study contributes to the field of religion and local culture by showing that social piety within the Galih Warangka Jati Association is shaped by both religious teachings and long-standing cultural ethics. The solidarity among members of the Galih Warangka Jati Association proves that social harmony in Javanese society is achieved through interactions born from religious devotion and inclusive cultural preservation.